The Effect of IT on After-sales Service in Small- and Medium-Sized Industries - Abdulkadir Özdemir; Hasan Asil (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In a world where competition is based on quality of service, quality distance between products becomes smaller day by day. Nowadays, after-sales service can be considered as an inseparable part of industrial products. The development of IT has paved the way for offering better services for customers in a shorter time in a way that these days it is called the electronic after-sales service. Based on this, the present research has analyzed the effect of using IT on after-sales service in small- and medium-sized industries. This research is a causal or a posteriori one which tries to answer the question of whether the use of IT can influence the quality of after-sales service offered by small- and medium-sized industries. According to results with a certainty level of %5, IT influences the accessibility of after-sales service in small- and medium-sized industries.